1998
DOI: 10.1097/00002060-199805000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Referral Patterns for Musculoskeletal Disorders1

Abstract: The purpose of this study was to determine the relationship between medical student knowledge and exposure to physiatry and the student's referral patterns for musculoskeletal disorders. Surveys were mailed to senior medical students at five United States medical schools across the country with a response rate of 26% (n=191). Five common musculoskeletal and neurologic disorders were presented as clinical vignettes and the student was asked to assume the role of a primary care physician and refer the patient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[3][4][5][6][7][8][9] There are various levels of familiarity and attitude toward the different areas of PM&R; however, the field as a whole is becoming more well-known as medical students start to recognize the value of physiatric skillsets in enhancing their understanding of how to comprehensively evaluate, diagnose, and treat a wide range of pathologies. [10][11][12][13] A prior 16-item, 130-factor questionnaire administered to graduating PM&R residents by DeLisa et al found that some of the most popular factors influencing resident decisions for residency programs included: "flexibility for family obligations, opportunities to make a difference in peopleʼs lives, interest in helping people, type of patient problem encountered, and consistency with the personality." 14 Given the increasing popularity of PM&R and a lack of a dedicated study evaluating the PM&R residency websites and online content, we found a need to further address this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] There are various levels of familiarity and attitude toward the different areas of PM&R; however, the field as a whole is becoming more well-known as medical students start to recognize the value of physiatric skillsets in enhancing their understanding of how to comprehensively evaluate, diagnose, and treat a wide range of pathologies. [10][11][12][13] A prior 16-item, 130-factor questionnaire administered to graduating PM&R residents by DeLisa et al found that some of the most popular factors influencing resident decisions for residency programs included: "flexibility for family obligations, opportunities to make a difference in peopleʼs lives, interest in helping people, type of patient problem encountered, and consistency with the personality." 14 Given the increasing popularity of PM&R and a lack of a dedicated study evaluating the PM&R residency websites and online content, we found a need to further address this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Our result is in line with Abramson's study at Harvard medicine school, suggesting that senior medical students' referral patterns strongly correlated with the knowledge of PMR. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%